Awareness and Perception of Plant-Based Diets for the Treatment and Management of Type 2 Diabetes in a Community Education Clinic: A Pilot Study. (31st January 2015) - Lee, Vincent; McKay, Taylor; Ardern, Chris I.
Abstract : Objective . To assess awareness, barriers, and promoters of plant-based diet use for management of type 2 diabetes (T2D) for the development of an appropriate educational program. Design . Cross-sectional study of patients and healthcare providers. Setting . Regional Diabetes Education Centre in ON, Canada. Participants . n = 98 patients attending the Diabetes Education Centre and n = 25 healthcare providers. Variables Measures . Patient questionnaires addressed demographics, health history, and eating patterns, as well as current knowledge, confidence levels, barriers to, promoters of, and interests in plant-based diets. Staff questionnaires addressed attitudes and current practice with respect to plant-based diets. Analysis . Mean values, frequency counts, and logistic regression (alpha = 0.05). Results . Few respondents (9%) currently followed a plant-based diet, but 66% indicated willingness to follow one for 3 weeks. Family eating preferences and meal planning skills were common barriers to diet change. 72% of healthcare providers reported knowledge of plant-based diets for diabetes management but low levels of practice. Conclusions and Implications . Patient awareness of the benefits of a plant-based diet for the management of diabetes remains suboptimal and may be influenced by perception of diabetes educators and clinicians. Given the reported willingness to try (but low current use of) plant-based diets, educational interventions targeting patient and provider level knowledge are warranted.